THE IMPACT OF AUTOMATION AND DIGITALIZATION ON THE COMMERCIAL MARKET IN THE REPUBLIC OF MOLDOVA - Lida CUCOȘ (Eastern European Journal of Regional Studies, 2025)
The purpose of this study is to analyze the effects of automation and digitization on the commercial sector of the Republic of Moldova, with particular attention to the benefits and challenges associated with technological transformation. The study emphasizes the ways in which digital tools and automation affect market accessibility, trade efficiency, and general economic dynamics. The uniqueness of this study lies in its multidisciplinary methodology, which combines technological and policy perspectives on digitalization with economic analysis. The article looks at how digital tools can improve business operations, lower transaction costs, and boost competitiveness. It also examines how automation transforms business models, increases productivity, and fosters innovation in the Republic of Moldova's trade sector. The study finds that SMEs in Moldova show a 40% adoption rate of digital payment tools, compared to 95% in large enterprises, highlighting the digital divide. The global reliance on automation and digitalization in economic activity underscores the relevance of this study. In order to stay competitive and guarantee long-term economic resilience, the Republic of Moldova must incorporate these technologies into its trade policies and business plans. The report offers information on how the Republic of Moldova can use digital transformation to support long-term development and increase its market share abroad. The methodology combines policy evaluation, statistical interpretation of digital trade data, and bibliographic analysis to assess the effects of automation and digitalization. These approaches give a thorough assessment of how automation and digitization have affected the Republic of Moldova's business environment and offer practical suggestions for companies and policymakers. In summary, the interaction of automation, digitization, and trade growth highlights the need for the Republic of Moldova to enact progressive policies that encourage technological advancement. The nation will be able to improve trade efficiency, encourage innovation, and fortify its economic resilience in the face of international challenges by adopting a strategic approach to automation and digital tools.